A vertente Vico - Gonçalves, Celso Eduardo Mendes (2011)
Vico s Scienza nuova introduces a proposal to science the Vico Variable which is clearly different from the prevailing variable, that of Modern Science as we understand it today, based on Newton s Mechanicism and in Descartes Rationalism, anchored in the Enlightenment of the 18th century and established, once and for all, in Comte s Positivism. In Vico, metaphysics no longer busies itself with the contemplation of and speculation about God, to bring its focus down to earth and seek, in History, that which had, until then, sought in the Divine Mind. To him, the knowledge of human affairs is that which can answer the question characteristic of all times concerning what Man is. The civil world of the Scienza nuova develops in the metaphysical realm, to whose study the new art of criticism is developed: a synergy between philosophical criticism and philological investigation, leading to Vico s hermeneutics, which takes advantage both of Reason and of the faculties of the spirit. In this hermeneutics, microcosm and macrocosm, man and society, particular and universal, are synthesized in constant analogies; the theory of the verum ipso factum is originally applied and the common sense of humanity becomes the supreme objective principle of historic evolution (a manifestation of Divine Providence) and as a subjective ground of a historic understanding. So as to situate nations in the development of the eternal ideal history , to evaluate its degrees of civility and the risks it is subject to, the Scienza nuova proposes, also, a diagnostic art, from which one may criticize the way which knowledge (Science and Education) is considered by the moderns in this time. Such criticism is not restricted to observations and considerations, but it sets the groundwork for an action it is, therefore, a Political Science through the proposal of a focus that is able to overcome the empire of the Mathesis Universalis, and thus, to contemplate, equally, the possibility of knowledge of the Ethical, Political and Human universes, interacting in a selfsame science. The Vico Variable is not only a way that has been forsaken on the road of the development of science; something which might have been. It is a philosophical orientation which privileges the practical life, the understanding of human behavior and civil life, which can be extended to thinkers who came after Vico, whose ideas allow the identification with outstanding aspects of his thought; a philosophical orientation which, identified with the emphasis Pico della Mirandola gave upon the Dignity of Man, can represent the emancipation of humanity